Implementasi Reward Dan Punishment Dalam Membentuk Kedisiplinan Sholat Dhuhur Berjamaah - Novika wahyu Hatutik; Pristiwiyanto (LPPM Institut Al Azhar Menganti Gresik, 2022)
The purpose of this study was to find out: 1) the process of implementing reward and punishment in forming the discipline of congregational midday prayers at SMA Negeri 1 Kedamean Gresik. 2) the results of the process of implementing reward and punishment in forming the discipline of praying dhuhr in congregation at SMA Negeri 1 Kedamean Gresik. Research conducted by the author using a qualitative descriptive method of field research using the case study method. The results of this study are 1) The process of implementing reward and punishment to be able to discipline students in congregational noon prayers at SMA Negeri 1 Kedamean Gresik is quite good. 2) By holding the Dhuhr prayer in congregation at SMA Negeri 1 Kedamean Gresik, it is hoped that all students can understand and have awareness of the obligation to pray, especially praying in congregation.